Trust Management VIII 8th IFIP WG 11.11 International Conference, IFIPTM 2014, Singapore, July 7-10, 2014. Proceedings - Zhou, Jianying; Gal-Oz, Nurit; Zhang, Jie.; Gudes, Ehud.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 8th IFIP WG 11.11 International Conference on Trust Management, IFIPTM 2014, held in Singapore, in July 2014. The 12 revised full papers and 5 short papers presented were carefully reviewed and selected from 36 submissions. In addition, the book contains one invited paper. The papers cover a wide range of topics focusing on the following main areas: trust and reputation models; privacy issues and social and behavioral models of trust; the relationship between trust and security; trust under attacks and trust in the cloud environment.
The Importance of Trust in Computer Security -- Trust MUSE: A Model-Driven Approach for Trust Management -- Reusability for Trust and Reputation Systems -- On Robustness of Trust Systems -- Design of Intrusion Sensitivity-Based Trust Management Model for Collaborative Intrusion Detection Networks -- Exploiting Trust and Distrust Information to Combat Sybil Attack in Online Social Networks -- Anomaly Detection for Mobile Device Comfort -- Improving the Exchange of Lessons Learned in Security Incident Reports: Case Studies in the Privacy of Electronic Patient Records -- A Privacy Risk Model for Trajectory Data -- Providing Trustworthy Advice Online: An Exploratory Study on the Potential of Discursive Psychology in Trust Research -- Extending Trust Management with Cooperation Incentives: Achieving Collaborative Wi-Fi Sharing Using Trust Transfer to Stimulate Cooperative Behaviours -- A Calculus for Trust and Reputation Systems -- Knots Maintenance for Optimal Management of Trust Relations -- On the Tradeoff among Trust, Privacy, and Cost in Incentive-Based Networks -- Reputation-Based Cooperation in the Clouds -- Introducing Patient and Dentist Profiling and Crowdsourcing to Improve Trust in Dental Care Recommendation Systems -- Abstract Accountability Language -- Trust Assessment Using Cloud Broker.
Keywords: Computer science; Computer security; Computers; Computers and civilization; Computer Science; Computers and Society; Systems and Data Security; Information Systems and Communication Service; Electronic books